Modeling heat distribution with the use of a non-integer order, state space model - Oprzędkiewicz, Krzysztof; Gawin, Edyta; Mitkowski, Wojciech (1946- ) (Zielona Góra: Uniwersytet Zielonogórski)
A new, state space, non-integer order model for the heat transfer process is presented. The proposed model is based on a Feller semigroup one, the derivative with respect to time is expressed by the non-integer order Caputo operator, and the derivative with respect to length is described by the non-integer order Riesz operator. Elementary properties of the state operator are proven and a formula for the step response of the system is also given. The proposed model is applied to the modeling of temperature distribution in a one dimensional plant. Results of experiments show that the proposed model is more accurate than the analogical integer order model in the sense of the MSE cost function.
Keywords: non-integer order systems; heat transfer equation; infinite dimensional systems; Feller semigroups